Class Iıı Malocclusıons And Orthognatıc Surgery - Ata Ümit Aksoy; Ege Özgentaş (Galenos Yayinevi, 1989)
The object of treatment in skeletal class III malocclusions is to improve the skeletal imbalance by orthopedic forces and to improve tooth alignment and establish intercuspal relations by orthodontic means, however, in severe skeletal class III after growth has terminated, the effect of treatment by orthodontics only is limited because of abnormal relationships between the jaws. Severe malocclusions in adults usually cannot be treated successfully without orthognatic surgery in concert with orthodontics. Both techniques are neccessary because orthognatic surgery frequently cannot produce precise alignment of teeth. In this article, a case treated by orthodontics and orthognatic surgery has been presented.